2018
DOI: 10.3389/fpls.2018.00237
|View full text |Cite
|
Sign up to set email alerts
|

High Throughput Determination of Plant Height, Ground Cover, and Above-Ground Biomass in Wheat with LiDAR

Abstract: Crop improvement efforts are targeting increased above-ground biomass and radiation-use efficiency as drivers for greater yield. Early ground cover and canopy height contribute to biomass production, but manual measurements of these traits, and in particular above-ground biomass, are slow and labor-intensive, more so when made at multiple developmental stages. These constraints limit the ability to capture these data in a temporal fashion, hampering insights that could be gained from multi-dimensional data. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
254
1
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 253 publications
(264 citation statements)
references
References 71 publications
8
254
1
1
Order By: Relevance
“…Morphological parameters, such as plant height, stem diameter, leaf area or leaf area index (LAI), leaf angle, stalk length, and in-plant space [1], can be determined with LiDAR (light detection and ranging). Research on phenotyping using LiDAR often focusses on one specific crop, for example, wheat [2,3] or cotton [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Morphological parameters, such as plant height, stem diameter, leaf area or leaf area index (LAI), leaf angle, stalk length, and in-plant space [1], can be determined with LiDAR (light detection and ranging). Research on phenotyping using LiDAR often focusses on one specific crop, for example, wheat [2,3] or cotton [4].…”
Section: Introductionmentioning
confidence: 99%
“…good correlation with in situ field measurements of plant height. Sun et al [4] published an R 2 of 0.98 for cotton plants, [2] published an R 2 of 0.99 for wheat, and [7] showed an R 2 of 0.90 for wheat. These studies show the capability of LiDAR to measure basic phenotypes such as plant height.…”
mentioning
confidence: 99%
“…Measurement of plant height using a ruler has long been the traditional approach [12,16,17]. Assessment of plant height from images is a far more complex process as it necessitates the estimation of depth in physical units; in discipline terms, a so-called depth map is reconstructed from multiple images of a canopy taken from slightly different viewpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Relevant work in this area has shown that accurate estimates are possible and indeed preferable given their objectivity and accuracy, compared with manual measurements, which can be subjective, as well as incomplete [5]. An alternative method, light detection and ranging (LiDAR), uses an active laser sensor to non-destructively measure canopy height with high accuracy [17].…”
Section: Introductionmentioning
confidence: 99%
“…By scanning across a physical area with multiple sensors or by grid-serpentine sampling with a single sensor, a three-dimensional point cloud can be obtained. Lidar has demonstrated accurate predictions (R 2 > 0.80) for crop density in wheat (Triticum aestivum L.; Saeys et al, 2009;Hosoi and Omasa, 2009) Zhang and Grift, 2012), rice (Oryza sativa L.; Tilly et al, 2014), and maize (Zea mays L.; Luo et al, 2016); canopy volume in tree species (Rosell et al, 2009); and biomass in maize (Luo et al, 2016), alfalfa (Medicago sativa L.; Noland et al, 2018), and wheat (Jimenez-Berni et al, 2018). Numerous other forage crops have exhibited moderate to high correlations between lidar and biomass (Freeman et al, 2007;Schaefer and Lamb, 2016;Ghamkhar et al, 2018).…”
Section: Hairy Vetch (Vicia Villosamentioning
confidence: 99%